CHARACTERIZATION OF THE VULCANICLASTIC SANDSTONE RESERVOIR, AIR BENAKAT FORMATION, JAMBI - SWASTIKA (NIM: 22013022), ARIF
Meruap field that located on South Sumatra Basin, administratively is a part of Sarolangun Regency, Jambi Province. It is one of profilic oil field in that area with vulcaniclastic rocks as a reservoir target. The type of reservoir is not common in Indonesian Basin, therefore the study about this reservoir type become important to be researched. Aim of this study is to identify reservoir characteristics based on depositional facies and rock type for estimating the reserve more accurate. This study using ‘induction-accumulative’ mind set supported by hypothesis proofment based on the valid rule and also integrating the secondary data includes seismic 3D data, 32 wireline log data and 5 core data. Data has been collected, processed and analyzed using depositional facies, petrophysics, rock typing and geomodeling analyses through geostatistics method. Based on depositional facies analysis, Sandstone A to D were deposited in transition zone, classified as Estuary with 5 facies association are fluvial, sand bar, mixed flat, mud flat, and marsh. Shale volume and radioactive content could be a guidance to determine reservoir and non-reservoir by petrophysical assessment. There are 6 rock type based on rock typing analysis using Hydraulic Flow Unit method. Facies and petrophysical properties have been distributed along the paleo-current trend from FMI data and considering zone/layer thickness. Differences of rock type are affected by genetic unit and take a significant contribution to reservoir characteristics of Air Benakat Formation in Meruap Field.